Cobalt catalyst with rich mesoporous structure as well as preparation method and application of cobalt catalyst
By using solvent heat treatment method in the preparation of cobalt-based catalysts, an alumina-supported cobalt-based catalyst with rich mesoporous structure and high uniformity Co2+ distribution was prepared, which solved the problems of low catalytic efficiency and poor stability in the hydrogenation of carbon dioxide to methanol reaction of existing cobalt-based catalysts, achieving efficient and stable catalytic performance and reducing costs.
Patent Information
- Application Number
- CN202411790303.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-28
AI Technical Summary
The existing cobalt-based catalysts have low catalytic efficiency and poor stability in the hydrogenation of carbon dioxide to methanol. This is mainly because Co3O4 nanoparticles are easily reduced to metal Co during the reaction and formed with carbon deposits, resulting in rapid deactivation of the catalyst.
By dissolving the aluminum source and the cobalt source in a mixed solution of low-carbon chain organic alcohol, combined with a solvent heat treatment method with droplet addition and program heating, an alumina-supported cobalt-based catalyst with rich mesoporous structure and high uniformity Co2+ distribution was prepared.
The catalyst has a high specific surface area and pore volume, a uniform mesoporous pore size, and a highly uniform dispersed Co2+ active species, which significantly improves catalytic activity, methanol selectivity and stability, and has a low cost.
Smart Images

Figure CN119701956A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of inorganic porous catalytic materials, and in particular relates to a cobalt-based catalyst with a rich mesoporous structure and a preparation method and application thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Methanol is an important basic organic raw material in the petrochemical industry. It is used to produce a variety of chemical products and can also be used as a fuel and a raw material for producing hydrogen. At present, the global methanol production capacity is about 140 million tons. The world's industrialized methanol production process mainly uses coal and natural gas as raw materials to produce synthesis gas and synthesize methanol. The methanol production process consumes a large amount of fossil energy and is accompanied by carbon dioxide emissions. It also has disadvantages such as high reaction pressure.
[0004] As the most abundant renewable raw material, the production of high value-added chemicals using carbon dioxide as a carbon source or oxygen source can not only protect the increasingly depleted fossil energy, but also reduce the emission of greenhouse gas carbon dioxide. Therefore, the production of methanol by coupling carbon dioxide as a carbon source with green hydrogen produced from renewable energy has attracted great attention from researchers.
[0005] At present, the catalysts used in the production process of carbon dioxide hydrogenation to produce methanol mainly include copper-based, cobalt-based and mixed oxide catalysts. Among them, cobalt-based catalysts have good application prospects in the field of carbon dioxide hydrogenation catalysis due to their excellent catalytic performance. 3+ For species, Co 2+ Species have stronger activation ability for CH bonds in hydrocarbons, and Co 2+ Highly uniform dispersion of active components is beneficial to improving the catalytic performance of cobalt-based catalysts for hydrogenation reactions. However, the cobalt species on the surface of cobalt-based catalysts prepared by traditional preparation methods are mainly Co3O4 nanoparticles with relatively poor dispersion. In the process of carbon dioxide hydrogenation to methanol, Co3O4 is easily reduced to metallic Co, accompanied by the formation of a large amount of carbon deposits, causing the catalyst to deactivate quickly. Summary of the invention
[0006] In view of the key problems of low catalytic efficiency and poor stability of cobalt-based catalysts for catalyzing the hydrogenation of carbon dioxide to methanol in the prior art, the purpose of the present invention is to provide a cobalt-based catalyst with a rich mesoporous structure and a preparation method and application thereof. The cobalt-based catalyst has a high specific surface area and pore volume, uniform mesopore diameter, and the cobalt active species can be highly uniformly dispersed at the near-atomic level, and can be applied to the hydrogenation of carbon dioxide to methanol.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a cobalt-based catalyst having a rich mesoporous structure, comprising the following steps:
[0009] dissolving an aluminum source and a cobalt source in a mixed solution of two low-carbon chain organic alcohols to obtain a clear solution;
[0010] Under vigorous stirring, water is added dropwise to the clear solution, and the solution is allowed to stand for a set aging time to obtain an aluminum sol in which cobalt ions are dissolved;
[0011] The aluminum sol containing the dissolved cobalt ions is subjected to a temperature program in a closed space to perform a solvent thermal treatment to obtain a surface of the aluminum sol uniformly grafted with Co 2+ Ionic alumina nanogel;
[0012] The alumina nanogel is dried and calcined to obtain a cobalt-based catalyst with a rich mesoporous structure.
[0013] Deionized water is slowly added dropwise to a mixed solution of two mutually soluble low-carbon chain organic alcohols in which an inorganic cobalt source and an aluminum source are dissolved. By taking advantage of the difference in polarity of the two low-carbon chain organic alcohols and combining the regulation of the deionized water drop acceleration rate and the hydrolysis temperature, the hydrolysis-polymerization rate of the Al species in the solution is regulated. After aging treatment, an aluminum sol containing a large amount of Al-OH species on the surface and adsorbing a layer of water molecules is obtained. The polymerization rate and degree of Al-OH species in the aluminum sol are regulated by adjusting the heating rate and the solvent thermal treatment temperature and time. At this time, the Co in the synthesis system 2+ Highly uniformly dispersed in water molecules. Other organic solvents cannot form Al-OH species with aluminum sol.
[0014] Subsequently, the aluminum sol containing Co ions was subjected to a programmed temperature-raising solvent thermal treatment. The heating rate, solvent thermal treatment temperature and time were adjusted to regulate the polymerization rate and degree of Al-OH species in the aluminum sol, while promoting the polymerization of Co dissolved in the water molecule layer. 2+ Hydrolysis reaction occurs to generate divalent cobalt hydroxyl species, which are used to undergo high-temperature polymerization reaction with Al-OH species on the surface of alumina nanoparticles in the sol to generate Co 2+ -O-Al bond, thus obtaining a highly uniform surface grafted with a large amount of Co 2+ of alumina nanogel.
[0015] Finally, through drying and calcination treatment, an alumina-supported cobalt-based catalyst with a high specific surface area, rich pore structure, and highly uniform dispersion of divalent cobalt active species at a near-atomic level is obtained.
[0016] In some embodiments, the aluminum source is selected from one or a combination of aluminum isopropoxide, aluminum isobutoxide, aluminum tert-butoxide, aluminum nitrate, aluminum chloride, or aluminum sulfate.
[0017] In some embodiments, the cobalt source is selected from one or a combination of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, cobalt sulfate heptahydrate, or cobalt phosphate.
[0018] In some embodiments, the low-carbon chain organic alcohol is anhydrous ethanol, propanol, isopropanol, n-butanol, isobutanol or tert-butanol.
[0019] Preferably, the mixture of two low-carbon chain organic alcohols is a mixture of ethanol and isopropanol, and the volume ratio of ethanol to isopropanol is 1:0.8-1.2, preferably 1:1.
[0020] In some embodiments, the molar ratio of the aluminum source, the cobalt source, water, and the alcohol is 20-100:1-10:10-200:200-1000.
[0021] In some embodiments, the temperature of static aging is 20-50° C., and the time of static aging is 2-5 h.
[0022] In some embodiments, the programmed temperature step is: heating from room temperature to 50-80°C at a heating rate of 2-10°C / min and maintaining for 6-24h, then heating to 80-140°C and maintaining for 1-5h, and finally heating to 100-200°C and maintaining for 6-24h.
[0023] Room temperature refers to the ambient temperature, which is generally 20-30℃.
[0024] In some embodiments, the calcination temperature is 550-700° C., and the calcination time is 4-7 hours.
[0025] In a second aspect, the present invention provides a cobalt-based catalyst with a rich mesoporous structure, which is prepared by the preparation method.
[0026] The catalyst has a high specific surface area and pore volume, uniform mesopore diameter, and divalent cobalt active species can be highly uniformly dispersed at the near-atomic level. The resulting cobalt-based catalyst with rich mesoporous structure can be used in the reaction of carbon dioxide hydrogenation to methanol, and shows high catalytic activity, methanol selectivity and stability.
[0027] In some embodiments, the specific surface area of the mesoporous cobalt-based catalyst is 200 to 420 m 2 / g, pore volume is 0.4~1.0cm 3 / g, pore size is 1.0-8.0nm.
[0028] Co 2+The active components can be highly uniformly dispersed on the catalyst surface at a near-atomic level.
[0029] In a third aspect, the present invention provides the use of the cobalt-based catalyst with rich mesoporous structure in catalyzing the hydrogenation of carbon dioxide to produce methanol.
[0030] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0031] The cobalt-based catalyst with rich mesoporous structure described in the present invention has a high specific surface area and pore volume, a uniform pore structure, and the divalent cobalt active species can achieve highly uniform dispersion at the near-atomic level, which is not only conducive to the rapid diffusion and transfer of reaction molecules, but also can increase the contact probability between the reaction molecules and the divalent cobalt active components, so as to improve the catalytic activity and stability of the cobalt-based catalyst for the hydrogenation of carbon dioxide to methanol.
[0032] The preparation method of the present invention is simple and easy to implement, with high reproducibility, and the use of an inorganic cobalt source can greatly reduce the preparation cost of a cobalt-based catalyst. The use of the obtained cobalt-based catalyst with a rich mesoporous structure can significantly improve the methanol production efficiency in the carbon dioxide hydrogenation to methanol reaction, and has practical significance for the industrial application of the carbon dioxide hydrogenation to methanol process and the efficient utilization of carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0034] Figure 1 This is the XRD spectrum of the cobalt-based catalyst with rich mesoporous structure prepared in Example 1.
[0035] Figure 2 This is the element mapping spectrum of the cobalt-based catalyst with rich mesoporous structure prepared in Example 1.
[0036] Figure 3 The N2 adsorption-desorption isotherm (A) and the corresponding pore size distribution curve (B) of the cobalt-based catalyst with rich mesoporous structure prepared in Example 1.
[0037] Figure 4 This is a graph showing the change trend of carbon dioxide conversion rate and methanol selectivity of the cobalt-based catalyst with rich mesoporous structure prepared in Example 1 as a function of reaction time.
[0038] Figure 5 This is a trend chart showing the catalytic performance of the cobalt-based catalyst with rich mesoporous structure prepared in Example 1 as a function of the number of regenerations. DETAILED DESCRIPTION
[0039] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0040] The activity evaluation of the catalyst in the present invention is carried out in a self-made high-pressure fixed-bed reactor. The activity evaluation process of the carbon dioxide hydrogenation to methanol catalyst is briefly described as follows:
[0041] The various raw materials or reagents used in the embodiments of the present invention are not particularly limited in their sources, and are all conventional products that can be purchased commercially, or can be prepared according to conventional methods well known to those skilled in the art.
[0042] Example 1.
[0043] Under strong stirring, 2.06 g of cobalt chloride hexahydrate and 20.42 g of aluminum isopropoxide were added to a mixed alcohol solution containing 36.80 g of ethanol and 36.10 g of propanol to obtain a clear solution. Subsequently, under strong stirring at 35°C, 1.8 g of deionized water was added dropwise to the mixed solution at a drop rate of 10 ml / min to promote the hydrolysis reaction of aluminum isopropoxide. After standing and aging for 5 hours, a solution containing Co dissolved therein was obtained. 2+ Aluminum sol;
[0044] Then, the obtained sol was placed in a sealed hydrothermal reactor for a three-step solvothermal treatment (specifically: heating to 60°C at a rate of 5°C / min, maintaining for 24 h, then heating to 90°C for 3 h, and finally heating to 110°C for 24 h) to obtain a surface uniformly grafted Co 2+ of alumina nanogel.
[0045] Finally, after drying at 70°C for 12 h and calcining at 550°C for 5 h, a cobalt-based catalyst with rich mesoporous structure was obtained.
[0046] Depend on Figure 1 It can be seen from the high-angle XRD pattern that no obvious diffraction peaks were detected in the sample, indicating that alumina exists in an amorphous form and the Co species on its surface are highly uniformly dispersed.
[0047] Elemental mapping analysis results ( Figure 2 ) further confirmed that Co, O, and Al species can be highly uniformly dispersed at the near-atomic level throughout the sample. The elemental composition analysis of the selected area showed that the Co / Al ratio was 0.087, which is exactly the same as the Co / Al ratio of the sample preparation feed.
[0048] Depend on Figure 3The N2 adsorption-desorption isotherm (A) and the corresponding pore size distribution curve (B) show that the sample exhibits a type IV adsorption isotherm and an H2-type hysteresis loop, and shows a very steep capillary condensation curve in the relative pressure range of 0.5 to 0.8 (e.g. Figure 3 A), indicating that the sample has uniformly distributed and interconnected mesopores (as shown in 3B). By calculation, the specific surface area of the sample is 329m 2 / g, pore volume 0.62cm 3 / g, and the pore size is 5.72nm.
[0049] The sample prepared as above was used as a catalyst for the hydrogenation of carbon dioxide to produce methanol, and the catalytic performance of the catalyst was investigated.
[0050] The reaction was carried out in a high-pressure micro fixed-bed reactor, into which 0.30 g of catalyst with a particle size of 40-60 mesh was loaded into a stainless steel reaction center with a diameter of 6 mm.
[0051] The temperature was raised to 550°C at a rate of 10°C / min under a nitrogen atmosphere, and then a mixture of CO2 and H2 was introduced, the volume ratio of CO2 and H2 was 1:3, and the gas flow rate was 20 mL / min. The composition of the reaction product was analyzed by GC-4000A gas chromatograph.
[0052] Catalyst evaluation results ( Figure 4 ) showed that during the 30h reaction process, the selectivity of the catalyst for the target product methanol always remained above 99%. When the reaction time reached 20h, the carbon dioxide conversion rate was as high as 63% or more, and then slowly deactivated. When the reaction time reached 30h, the carbon dioxide conversion rate still remained above 53%. It can be seen that the catalyst has excellent carbon dioxide hydrogenation to methanol reaction activity, methanol selectivity and stability.
[0053] More importantly, the catalyst did not show significant changes in its conversion rate of carbon dioxide and selectivity for the target product methanol during repeated regeneration after calcination at 550°C for 2 h ( Figure 5 ), indicating that the catalyst has excellent regeneration and reuse performance.
[0054] Example 2
[0055] Under strong stirring, 2.52g of cobalt chloride hexahydrate and 24.63g of aluminum isobutoxide were added to a mixed alcohol solution containing 36.80g of ethanol and 44.47g of isobutanol to obtain a clear solution. Subsequently, under strong stirring at 35°C, 3.6g of deionized water was added dropwise to the mixed solution at a drop rate of 5ml / min to promote the hydrolysis reaction of aluminum isobutoxide. After standing and aging for 5h, a solution containing Co dissolved therein was obtained. 2+ Aluminum sol;
[0056] Then, the obtained sol was placed in a sealed hydrothermal autoclave for a three-step solvent thermal treatment (specifically: heating to 70°C at a rate of 5°C / min and maintaining for 12 hours, then heating to 100°C and maintaining for 5 hours, and finally heating to 100°C and maintaining for 24 hours) to obtain an alumina nanogel with divalent cobalt ions uniformly grafted on the surface.
[0057] Finally, after drying at 70°C for 24h and calcining at 550°C for 5h, a cobalt-based catalyst with rich mesoporous structure was obtained.
[0058] The characterization results of XRD, EDX and N2 adsorption-desorption confirmed that the prepared samples have high specific surface area and pore volume, uniform mesopore size distribution, and divalent cobalt active species can achieve highly uniform dispersion at the near-atomic level. The specific surface area of the sample is 377m 2 / g, pore volume 0.73cm 3 / g and the pore size is 6.95nm.
[0059] The reaction of hydrogenating carbon dioxide to produce methanol was carried out according to the reaction conditions in Example 1, and the catalytic performance of the sample of this example as a catalyst was investigated. During the 30h catalytic reaction, the selectivity of the catalyst for the target product methanol was always maintained above 98%, and the carbon dioxide conversion rate was as high as 67.30% at 18h of reaction, and then decreased to 50.21%. During the 5 times of regeneration and reuse of the catalyst, its performance of hydrogenating carbon dioxide to produce methanol did not change significantly.
[0060] Example 3
[0061] Under strong stirring, 2.52g of cobalt nitrate hexahydrate and 20.42g of aluminum isopropoxide were added to a mixed alcohol solution containing 36.80g of ethanol and 36.10g of isopropanol to obtain a clear solution. Subsequently, under strong stirring at 45°C, 5.4g of deionized water was added dropwise to the mixed solution at a drop rate of 7ml / min to promote the hydrolysis reaction of aluminum isopropoxide, and after standing and aging for 5h, an aluminum sol in which Co ions were dissolved was obtained;
[0062] Then, the obtained sol was placed in a sealed hydrothermal autoclave for a three-step solvent thermal treatment (specifically: heating to 100°C at a rate of 10°C / min and maintaining for 24 hours, then heating to 140°C and maintaining for 5 hours, and finally heating to 200°C and maintaining for 24 hours) to obtain an alumina nanogel with divalent cobalt ions uniformly grafted on the surface.
[0063] Finally, after drying at 120°C for 12 h and calcining at 550°C for 5 h, a cobalt-based catalyst with rich mesoporous structure was obtained.
[0064] XRD, SEM, N2 adsorption-desorption and other characterization results confirmed that the prepared sample has a rich pore structure and cobalt species are highly dispersed on the catalyst surface. The specific surface area of the sample is 350.23m 2 / g, pore volume 0.68cm 3 / g and the pore size is 7.638nm.
[0065] The reaction of hydrogenating carbon dioxide to produce methanol was carried out according to the reaction conditions in Example 1, and the catalytic performance of the sample of this example as a catalyst was investigated. During the 30h catalytic reaction, the selectivity of the catalyst for the target product methanol was always maintained above 98%, and the carbon dioxide conversion rate was as high as 65.65% at 18h of reaction, and then decreased to 52.32%. During the 5 times of regeneration and reuse of the catalyst, its performance of hydrogenating carbon dioxide to produce methanol did not change significantly.
[0066] Example 4
[0067] Under strong stirring, 2.52g of cobalt nitrate hexahydrate and 34.22g of aluminum isopropoxide were added to a mixed alcohol solution containing 36.80g of ethanol and 44.47g of tert-butyl alcohol to obtain a clear solution. Subsequently, under strong stirring at 50°C, 1.8g of deionized water was added dropwise to the mixed solution at a drop rate of 10ml / min to promote the hydrolysis reaction of aluminum isopropoxide, and after standing and aging for 5h, an aluminum sol in which Co ions were dissolved was obtained;
[0068] Then, the obtained sol was placed in a sealed hydrothermal autoclave for a three-step solvent thermal treatment (specifically: heating to 100°C at a rate of 10°C / min and maintaining for 12 hours, then heating to 140°C and maintaining for 2 hours, and finally heating to 200°C and maintaining for 24 hours) to obtain an alumina nanogel with divalent cobalt ions uniformly grafted on the surface.
[0069] Finally, after drying at 120°C for 12 h and calcining at 600°C for 5 h, a cobalt-based catalyst with rich mesoporous structure was obtained.
[0070] XRD, SEM, N2 adsorption-desorption and other characterization results confirmed that the prepared sample has a rich pore structure and cobalt species are highly dispersed on the catalyst surface. The specific surface area of the sample is 362.45m 2 / g, pore volume 0.55cm 3 / g and the pore size is 6.325nm.
[0071] The reaction of hydrogenating carbon dioxide to produce methanol was carried out according to the reaction conditions in Example 1, and the catalytic performance of the sample of this example as a catalyst was investigated. During the 30h catalytic reaction, the selectivity of the catalyst for the target product methanol was always maintained above 99%, and the carbon dioxide conversion rate was as high as 64.18% at 18h of reaction, and then decreased to 49.98%. During the 5 times of regeneration and reuse of the catalyst, its performance of hydrogenating carbon dioxide to produce methanol did not change significantly.
[0072] Example 5
[0073] Under strong stirring, 4.12g of cobalt chloride hexahydrate and 40.84g of aluminum isopropoxide were added to a mixed alcohol solution containing 73.60g of ethanol and 36.10g of isopropanol to obtain a clear solution. Subsequently, under strong stirring at 50°C, 7.2g of deionized water was added dropwise to the mixed solution at a drop rate of 10ml / min to promote the hydrolysis reaction of aluminum isopropoxide, and after standing and aging for 5h, an aluminum sol in which Co ions were dissolved was obtained;
[0074] Then, the obtained sol was placed in a sealed hydrothermal autoclave for a three-step solvent thermal treatment (specifically: heating to 70°C at a rate of 10°C / min and maintaining for 12 hours, then heating to 100°C and maintaining for 2 hours, and finally heating to 120°C and maintaining for 24 hours) to obtain an alumina nanogel with divalent cobalt ions uniformly grafted on the surface.
[0075] Finally, after drying at 120°C for 12 h and calcining at 600°C for 5 h, a cobalt-based catalyst with rich mesoporous structure was obtained.
[0076] XRD, SEM, N2 adsorption-desorption and other characterization results confirmed that the prepared sample has a rich pore structure and cobalt species are highly dispersed on the catalyst surface. The specific surface area of the sample is 336m 2 / g, pore volume 0.59cm 3 / g and the pore size is 5.856nm.
[0077] The reaction of hydrogenating carbon dioxide to produce methanol was carried out according to the reaction conditions in Example 1, and the catalytic performance of the sample of this example as a catalyst was investigated. During the 30h catalytic reaction, the selectivity of the catalyst for the target product methanol was always maintained above 98%, and the carbon dioxide conversion rate was as high as 58.33% at 18h of reaction, and then decreased to 50.02%. During the 5 times of regeneration and reuse of the catalyst, its performance of hydrogenating carbon dioxide to produce methanol did not change significantly.
[0078] Example 6
[0079] Under strong stirring, 2.52g of cobalt nitrate hexahydrate and 20.42g of aluminum isopropoxide were added to a mixed alcohol solution containing 36.80g of ethanol and 44.47g of n-butanol to obtain a clear solution. Subsequently, under strong stirring at 35°C, 3.6g of deionized water was added dropwise to the mixed solution at a drop rate of 10ml / min to promote the hydrolysis reaction of aluminum isopropoxide, and after static aging treatment for 5h, aluminum sol in which Co ions were dissolved was obtained;
[0080] Then, the obtained sol was placed in a sealed hydrothermal autoclave for a three-step solvent thermal treatment (specifically: heating to 100°C at a rate of 15°C / min and maintaining for 12 hours, then heating to 140°C and maintaining for 2 hours, and finally heating to 180°C and maintaining for 24 hours) to obtain an alumina nanogel with divalent cobalt ions uniformly grafted on the surface.
[0081] Finally, after drying at 120°C for 12 h and calcining at 700°C for 5 h, a cobalt-based catalyst with rich mesoporous structure was obtained.
[0082] XRD, SEM, N2 adsorption-desorption and other characterization results confirmed that the prepared sample has a rich pore structure and cobalt species are highly dispersed on the catalyst surface. The specific surface area of the sample is 260.33m 2 / g, pore volume 0.555cm 3 / g and the pore size is 4.836nm.
[0083] The reaction of hydrogenating carbon dioxide to produce methanol was carried out according to the reaction conditions in Example 1, and the catalytic performance of the sample of this example as a catalyst was investigated. During the 30h catalytic reaction, the selectivity of the catalyst for the target product methanol was always maintained above 97%, and the carbon dioxide conversion rate was as high as 48.21% at 18h of reaction, and then decreased to 43.23%. During the 5 times of regeneration and reuse of the catalyst, its catalytic performance of hydrogenating carbon dioxide to produce methanol did not change significantly.
[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a cobalt-based catalyst with a rich mesoporous structure, characterized in that: The steps include: dissolving an aluminum source and a cobalt source in a mixed solution of two low-carbon chain organic alcohols to obtain a clear solution; Under vigorous stirring, water is added dropwise to the clear solution, and the solution is allowed to stand for a set aging time to obtain an aluminum sol in which cobalt ions are dissolved; The aluminum sol containing the dissolved cobalt ions is subjected to a temperature program in a closed space to perform a solvent thermal treatment to obtain a surface of the aluminum sol uniformly grafted with Co 2+ Ionic alumina nanogel; The alumina nanogel is dried and calcined to obtain a cobalt-based catalyst with a rich mesoporous structure.
2. The method for preparing a cobalt-based catalyst with a rich mesoporous structure according to claim 2, characterized in that: The aluminum source is selected from one or a combination of aluminum isopropoxide, aluminum isobutoxide, aluminum tert-butoxide, aluminum nitrate, aluminum chloride or aluminum sulfate.
3. The method for preparing a cobalt-based catalyst with a rich mesoporous structure according to claim 2, characterized in that: The cobalt source is selected from one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, cobalt sulfate heptahydrate or cobalt phosphate or a combination thereof.
4. The method for preparing a cobalt-based catalyst with a rich mesoporous structure according to claim 2, characterized in that: The low-carbon chain organic alcohol is anhydrous ethanol, propanol, isopropanol, n-butanol, isobutanol or tert-butanol; Preferably, the mixture of two low-carbon chain organic alcohols is a mixture of ethanol and isopropanol, and the volume ratio of ethanol to isopropanol is 1:0.8-1.2, preferably 1:
1.
5. The method for preparing a cobalt-based catalyst with a rich mesoporous structure according to claim 2, characterized in that: The molar ratio of the aluminum source, the cobalt source, water and the alcohol is 20-100:1-10:10-200:200-1000.
6. The method for preparing a cobalt-based catalyst with rich mesoporous structure according to claim 2, characterized in that: The temperature for static aging is 20-50°C, and the time for static aging is 2-5h.
7. The method for preparing a cobalt-based catalyst with a rich mesoporous structure according to claim 2, characterized in that: The steps of programmed temperature increase are: heating from room temperature to 50-80°C at a heating rate of 2-10°C / min and maintaining for 6-24h, then heating to 80-140°C and maintaining for 1-5h, and finally heating to 100-200°C and maintaining for 6-24h.
8. The method for preparing a cobalt-based catalyst with rich mesoporous structure according to claim 2, characterized in that: The calcination temperature is 550-700°C and the calcination time is 4-7h.
9. A cobalt-based catalyst with rich mesoporous structure, characterized in that: Prepared by the preparation method of any one of claims 1 to 8; the specific surface area of the cobalt-based catalyst with rich mesoporous structure is 200 to 420 m 2 / g, pore volume is 0.4~1.0cm 3 / g, pore size is 1.0-8.0nm.
10. Use of the cobalt-based catalyst with rich mesoporous structure as claimed in claim 9 in catalytic hydrogenation of carbon dioxide to produce methanol.